The Effect of Local Wisdom-Based Training and Task Performance on Work Engagement in the Preservation of Pupur Bangkal as Traditional Skincare - Angriani, Maya Rezeki; Nurhayati; Tino Kemal Fattah; Faisal Reza; Zuyyina (Magister Administrasi Bisnis ULM, 2026)
This study aims to examine the effect of Local Wisdom-Based Training and Task Performance on Work Engagement in the preservation of Pupur Bangkal, a traditional skincare product from South Kalimantan, Indonesia. The research is grounded in the Resource-Based View (RBV), which posits that unique and inimitable resources, including culturally embedded human resources, can generate sustainable competitive advantage. A quantitative explanatory research design was employed using a saturated sample of 199 management students at Sari Mulia University who were associated with the local traditional industry context. Data were collected through a structured questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that Local Wisdom-Based Training and Task Performance simultaneously have a significant effect on Work Engagement. Partially, Local Wisdom-Based Training shows a significant and positive influence on Work Engagement, whereas Task Performance does not have a significant partial effect. These findings suggest that the internalization of cultural values, traditional knowledge, and authentic production processes plays a more critical role in fostering employees’ psychological attachment to work than merely achieving technical performance standards. In conclusion, Local Wisdom-Based Training emerges as the dominant predictor of Work Engagement, highlighting the importance of values-based human resource development in traditional industries. Integrating local wisdom into training programs is essential to strengthen employee engagement and support the sustainable preservation of culturally rooted products such as Pupur Bangkal